Influence of Gasification Operating Parameters on Performance of the Nong Bua Dual Fluidized Bed Gasification System in Thailand - Prasong, Malinee; Siriwongrungson, Vilailuck; Hongrapipat, Janjira; Rauch, Reinhard; Pang, Shusheng; Messner, Michael (My University, 2022)
Gasification system performance generally depends on feed moisture content, activity of bed material, gasifier and combustor temperatures, and scrubber media. The tar concentration and gas composition of product gas are two indicators of the gasification system performance. In this research, the effects of gasifier temperature and the activity of bed material on the tar concentration and gas composition of the product gas produced from a dual fluidized bed (DFB) gasification system power plant were investigated. The DFB gasification system power plant is located in Nong Bua district, Nakhon Sawan province, Thailand. Two periods of gasification operation were examined. These two periods were when the olivine was freshy activated and then after a period of operation. The gasifier temperature had several peaks during the operation, which caused the product gas composition to fluctuate. When the olivine had been used for a period, the percentage of hydrogen was approximately 3% higher than when the olivine had been freshly activated, and a lower heating value was observed, which was probably due to lower heating value of hydrogen. The tar concentration was substantially lower when compared with the freshly activated olivine. When the olivine was used for a period, the average tar concentration was 56±22 mg/Nm3 (this is after 95 h continuous operating time) while the average tar concentration of the freshly activate olivine was 872±125 mg/Nm3 (which was after 34.5 h continuous operating time). It was concluded that the average tar concentration and gas composition were influenced by the activity of the bed material and the gasification temperature.
Keywords: biomass gasification; dual fluidized bed gasifier; gravimetric tar; plant performance